Price and volume effects for stocks traded under the CPF approved investment scheme (AIS) : the new evidence - Ong, Chi Ning (2015)
The CPF Liberalisation Scheme was first announced on 26 January 1993 by our senior Minister, Mr Lee Kuan Yew. The announcement was welcomed by many businessmen and professionals, who see that it will help to boost the stock market and increase market liquidity. Our study examines the price and volume effects of AIS stocks and NAIS stocks under the above event. Hence, our empirical test covers the test period relating to the event date : 26 January 1993. Using daily prices and trading volumes of the SES All Singapore index and the stocks included in our AIS and NAIS samples from 20 August 1992 to 31 March 1993, the result of this study suggests that both AIS and NAIS stocks have insignificant price effects but significant increase in trading volumes.